Scenario framework for SYMOBIO 2.0: Summary of relevant scenarios, strategies and policy targets with a focus on Germany and the EU - Christian Lutz; Johannes Többen (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2023)
To determine footprints of the German bioeconomy, a scenario framework is needed in which consistent assumptions are made for framework data. This is particularly important for ex-ante considerations. The approach in SYMOBIO 1.0 builds on earlier work that has projected the EXIOBASE database into the future. For the continuation and improvement of the footprint calculations of the German bioeconomy in SYMOBIO 2.0, the question of the socio-economic framework arises again. In initial internal project discussions, consideration was given to developing not only a business-as-usual scenario but also an expected trends and/or a target scenario in which various political goals in the bioeconomy, agriculture and climate protection are achieved. It was decided to take a decision based on the scenario framework. This report serves the corresponding decision-making. The report is structured as follows: Section 2 briefly describes some background information such as current status, expected developments and future challenges of the bioeconomy, policy initiatives, and recent research regarding footprints of the bioeconomy. In section 3, a concept for the framework scenario is briefly presented and, as far as possible, quantified. Section 4 briefly discusses the principle of the intended implementation. A brief outlook closes the paper in section 5.
Keywords: C67; F6; Q17; Q57; 330; Bioeconomy; footprints; MRIO; scenarios bzw; Bioökonomie; Fußabdrücke; MRIO; Szenarien